Modele de organizare şi funcţionare a învăţământului profesional şi tehnic din România - Petrescu, Claudia; Neguț, Adriana (Calitatea Vieții, 2016)
In the context of knowledge society and increasing concerns for sustainable and inclusive growth, investment in human capital development have become indispensable and the interest in developing initial vocational and technical education has also intensified. In recent years, education policies have focused more and more on updating skills and their correlation to labour market requirements. An important contribution to synchronizing the two systems comes from work–based–learning component of education, which allows students to develop their practical skills in real employment context. Work-based-learning is integrated in various degrees in initial vocational and technical education programs in European countries and beyond, along with school-based-learning. In Romania, initial vocational and technical education has been destabilised by numerous reforms and has faced significant decline both in terms of attractiveness and number of students. The article reviews the main challenges faced by IVET system in Romania and presents the main models of initial vocational and technical education at European level. Without relying on an exhaustive analysis of current Romanian situation, but on the results of six case studies, the article presents the national models of IVET. The analysis is based on four main criteria: the importance of work-based-learning component in training students, partnership with social actors, management model and financing mechanisms.